Unravelling the Complex Na2CO3 Electrochemical Process in Rechargeable Na‐CO2 Batteries. Issue 13 (15th February 2023) - Tan, Chuan; Wang, Aiping; Cao, Deqing; Yu, Fengjiao; Wu, Yuping; He, Xiangming; Chen, Yuhui
Abstract: Rechargeable sodium‐carbon dioxide batteries utilize CO2 directly and use abundant and low‐cost sodium instead of lithium. Sodium carbonate is an important discharge product in Na‐CO2 batteries and its oxidative decomposition during charging determines cell performance (i.e., overpotentials and cyclability) but the decomposition mechanism has not been addressed yet. Herein, it is found that Na2 CO3 decomposition during the charging process follows a different pathway to lithium carbonate decomposition. It proceeds via a reactive CO3 − intermediate instead of a singlet oxygen intermediate, and thus CO and O2 evolution are not identified during charging. Calculation results show that the OO distance between two adjacent CO3 − in solid Na2 CO3 is longer than that in lithium carbonate and thus forming the C2 O6 2− dimer and singlet oxygen is kinetically disfavored in Na2 CO3 . Surprisingly, the carbon element in Na2 CO3 and carbon substrate can exchange via a Na2 CO3 C composite after ball milling. By forming the Na2 CO3 C composite, carbon can participate in the charging process and be fully oxidized. Therefore, designing a catalyst to encourage the reversible formation/decomposition of Na2 CO3 C might be the key to realizing the reversible cycling of Na‐CO2 batteries. Abstract : Na2 CO3 is an important discharge product of Na‐CO2 batteries, and its oxidative decomposition mechanism is important. Herein, it is found that its decomposition proceeds via a reactive CO3 − intermediate rather than a singlet oxygen. Surprisingly, the carbon element in Na2 CO3 and carbon substrate can exchange via a Na2 CO3 C composite after ball‐milling, which facilitates carbon oxidation on charging.